Water quality assessment of Kalan Malayer Dam Lake using NSFWQI index and its zoning using GIS - Hajar Merrikhpour; Bahare Lorestani; Mehrdad Cheraghi (علوم محیطی)
Introduction: In recent years, changes in the amount, distribution, and quality of surface water around the world have led to special attention to these resources. So, according to the economic concerns in the social development of countries, it is important to access water of good quality. The study aimed to investigate the quality of surface water samples taken from Lake Malayer Dam Lake using the Water Quality Index of the National Institutes of Health (NSFWQI). Material and methods: To evaluate the water quality of the dam lake, a total of 19 water samples were collected from different parts of the dam in May, June, September, October, and February, 2017-2018. The water parameters, including pH, soluble oxygen, total solids, oxygen biochemical demand, turbidity, temperature, nitrate, phosphate, and total coliform bacteria were measured and the effect of each parameter was calculated in the samples. Then, the water quality index was calculated. Also, the spatial variability of this index in the river and dam lake was done separately using Arc GIS software. Results and discussion: The results showed that due to the high budget of nitrate and phosphate, the concentration of these elements at the input flow was higher than the output flow. Also, the results of coliform bacteria showed that the Kalan dam in all seasons and all stations have microbial contamination that is higher than the standard limitation for drinking water. The lowest value of the NSFWQI index was obtained in the course of the river and the dam lake in May (59.1) and the highest value was obtained in February (74.4). According to the results, the quality of the water leaving the dam was average. The higher water quality in February was due to the low biological oxygen demand (BOD), which could be due to the increase in oxygen dissolution and the decrease in water temperature and vital activities (respiration of organisms and decomposition of organic matter). Conclusion: The results showed that the water quality in the studied stations in winter was generally more favorable due to the increasing volume of the water flow and the stored water behind the dam, the low temperature, and low agricultural activities. Agricultural activities at the beginning of the dam lake and the existence of villages near the river enter pesticides and chemical and animal fertilizers, which mainly contain pollutants such as nitrate and phosphate. Then, these pollutants move to the reservoir of the dam.